Effects of Preemptive Gabapentin on Postoperative Pain Control and Opioid Consumption after Abdominal Hysterectomy (The Planet, 2022)
Background: Preemptive analgesia is an analgesic state that is initiated before surgery in order to prevent the establishment of central sensitization evoked by the incisional and inflammatory injuries occurring during surgery and in the early postoperative period. Preemptive analgesia can both decrease the severity and duration of pain and also can delay the pain. There are different methods and techniques present now a days to obtain preemptive analgesia. Gabapentin is a drug which was introduced recently and it is used in various field of anaesthesia practice. Gabapentin have been shown to be beneficial in postoperative pain following various surgery. The present study was carried out to evaluate the effect of preemptive oral gabapentin on postoperative pain control and opioid consumption in patients undergoing abdominal hysterectomy. Method: In this prospective randomized double-blind study, Total 60 patients of ASA grade I, II planned for Total Abdominal Hysterectomy were selected randomly according to selection criteria. Sixty patients divided into two groups, 30 patients underwent total abdominal Hysterectomy received gabapentin 600 mg (Group-G) and 30 patients received placebo (Group-P) orally two hours prior induction of anesthesia.  All patients instructed preoperatively for the pain visual analogue scale (VAS) and verbal rating scale for measurement and assessment of the quality of pain. All patients were given 100 mg suppository diclofenac every 8 h.  If VAS score more than 4 a top up dose of pethidine 0.5mg/kg was administered intravenously. Total pethidine consumption during initial 12 hours postoperative period was recorded for each patient. Result: Patients in the placebo group had higher VAS score, just after operation during zero hour mean VAS score was 6.3±0.95 and 8.2±0.25 in group G & group P respectively. During the second hours compared with the gabapen¬tin groups, mean VAS score was 5.2±0.47 and 7.4±0.68 in group G & group P respectively. Six hours after the surgery, both groups showed downward trends of the pain VAS, but significantly in group G. Mean score was 4.1±0.32 and 6.2±0.51 in group G & group P respectively. Conclusion: Present study shows that pre-emptive use of oral Gabapentin significantly reduces the post-operative pain and reduces the opioid (pethidine) consumption in patient undergoing Total Abdominal Hysterectomy.
Keywords: Preemptive analgesia; gabapentine; postoperative pain; abdominal hysterectomy